DEVELOPMENT OF PRINCIPLES OF DCNET AND FLASH ENVIRONMENTS INTERACTION - A. V. Denisenko; A. A. Gursky (Автоматизация технологических и бизнес-процессов, 2016)
The question of implementation of the interface between the DCNET and Flash media is examined. Usage of the interface-based DCNET environment allows to reduce time and material costs for the development t and study of complicated technological system and to increase functional imaging capabilities compared to ActionScript.